1983
DOI: 10.1021/ed060p131
|View full text |Cite
|
Sign up to set email alerts
|

Flow chart for naming inorganic compounds

Abstract: The flow chart presented in this paper can aid students that are learning to name inorganic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…20−22 chemistry subjects, such as qualitative analysis, 23 point group classification, 24 reaction workup planning, 25 and naming inorganic compounds. 22 Moreover, the studies on nomenclature are generally about the nomenclature of inorganic compounds, 10,26,27 and organic compounds, 28,29 not coordination compounds. Given the importance of flowcharts in improving students' understanding and lack of studies on using flowcharts for naming coordination compounds, we hypothesized that flowcharts could be effective for identifying isomerism type and naming coordination compounds, which have many rules and instructions to memorize.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20−22 chemistry subjects, such as qualitative analysis, 23 point group classification, 24 reaction workup planning, 25 and naming inorganic compounds. 22 Moreover, the studies on nomenclature are generally about the nomenclature of inorganic compounds, 10,26,27 and organic compounds, 28,29 not coordination compounds. Given the importance of flowcharts in improving students' understanding and lack of studies on using flowcharts for naming coordination compounds, we hypothesized that flowcharts could be effective for identifying isomerism type and naming coordination compounds, which have many rules and instructions to memorize.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous research suggests that flowcharts are effective, advanced organizers for student learning. , In particular, several studies have indicated that flowcharts improve students’ understanding of directions, as compared to those given in prose format. Flowcharts have been used to teach various chemistry subjects, such as qualitative analysis, point group classification, reaction workup planning, and naming inorganic compounds . Moreover, the studies on nomenclature are generally about the nomenclature of inorganic compounds, ,, and organic compounds, , not coordination compounds.…”
Section: Introductionmentioning
confidence: 99%
“…A flowchart, which is a kind of graphic organizer, provides a holistic representation of facts and concepts and their relationships in an organized framework . Students can use this pedagogical tool until memorizing a set of rules becomes automatic . Where decision making is required (e.g., problem-solving processes), flowcharts are frequently used to represent procedural sequences .…”
Section: Introductionmentioning
confidence: 99%
“…As the author indicates, there are many chemical formula card games reported in this Journal, but there are also several methods intended for learning chemical nomenclature published in this Journal that I would like to mention. A literary review published since the 1980s describes games such as a Web-based mnemonic game published recently 2 and other games published previously, 3−8 computer programs, 9,10 activities based on flowcharts 11 and schemes, 12,13 procedures to determine oxoacid formulas, 14 mnemonic rules, 15 and specific methodologies. 16−18 In addition, there are other activities published in this Journal not categorized with the keyword term "Nomenclature/Units/ Symbols", but which can be used to learn this topic as well, such as the activity described by Pippins et al 19 Because students often have difficulty learning chemical nomenclature, it is important for teachers to use many different methods to improve the teaching of this subject: The more hands-on activities that can be employed to teach nomenclature, the better.…”
mentioning
confidence: 99%
“…As the author indicates, there are many chemical formula card games reported in this Journal , but there are also several methods intended for learning chemical nomenclature published in this Journal that I would like to mention. A literary review published since the 1980s describes games such as a Web-based mnemonic game published recently and other games published previously, computer programs, , activities based on flowcharts and schemes, , procedures to determine oxoacid formulas, mnemonic rules, and specific methodologies. …”
mentioning
confidence: 99%